EFFECTIVENESS OF UMBILICAL ARTERY DOPPLER EXAMINATION, CARDIOTOCOGRAPHY AND AMNIOTIC FLUID INDEX APPLIED IN EARLY INTRAPARTUM PERIOD IN DIAGNOSIS OF FETAL DISTRESS - Sezgin Dursun; Bulat Aytek Şık; Baki Erdem; Yılda Arzu Aba (Rojan GÜMÜŞ, 2017)
The present study aims to find an alternative solution to continuous monitoring with Cardiotocography (CTG) during intrapartum management process of pregnant women with no previous antenatal follow-up, and to diagnose low-risk pregnancies and avoid the financial burden and discomfort to the pregnant woman resulting from continuous monitoring. Randomly selected 114 term pregnant women with expected vaginal delivery, singleton pregnancies and no major fetal abnormalities were included in the study. Routine obstetric ultrasonography (USG) and uterine artery (UA) doppler measurements were administered. The pregnant women included in the study had an average gestation period of 38.3 ± 1.3, average age of 26.1 ± 5.3, average parity of 2.1 ± 1.5 and average infant birth weight of 3280 ± 442 g. 13 pregnant women were considered to have fetal distress following continuous monitoring with cardiotocography. Furthermore, decreased amniotic fluid index was detected in 9 of them. 10 cases were assessed to be pathological as a result of Uterine Artery Doppler examination. In two cases deemed pathological, fetal distress developed and found to be statistically insignificant. No statistically significant difference was found between decreased amniotic fluid index cases and non-decreased amniotic fluid index cases in terms of C-section application due to fetal distress. In our study, Cardiotocography + Amniotic Fluid Index measurement was determined to be the most valuable combination as the delivery room admission test.